Association of VEGF With Antianhedonic Effects of Repeated-Dose Intravenous Ketamine in Treatment-Refractory Depression - Zheng, Wei; Gu, Li-Mei; Zhou, Yan-Ling; Wang, Cheng-Yu; Lan, Xiao-Feng; Zhang, Bin; Shi, Hai-Shan; Wang, Dan-Feng; Ning, Yu-Ping (Frontiers in Psychiatry, 2021)
Objectives: To first explore the role of plasma vascular endothelial growth factor (VEGF) concentrations in ketamine’s antianhedonic effects, focusing on Chinese patients with treatment-refractory depression (TRD). Methods: Seventy-eight patients with treatment-refractory major depressive disorder (MDD) or bipolar disorder (BD) were treated with six ketamine infusions (0.5 mg/kg). Levels of anhedonia were measured using the Montgomery–Åsberg Depression Rating Scale (MADRS) anhedonia item at baseline, day 13 and day 26. Plasma VEGF concentrations were examined at the same time points as the MADRS. Results: Despite a significant reduction in anhedonia symptoms in individuals with treatment-refractory MDD (n=59) or BD (n=19) after they received repeated-dose ketamine infusions (p<0.05), no significant changes in plasma VEGF concentrations were found at day 13 when compared to baseline (p>0.05). The alteration of plasma VEGF concentrations did not differ between antianhedonic responders and nonresponders at days 13 and 26 (all ps>0.05). Additionally, no significant correlations were observed between the antianhedonic response to ketamine and plasma VEGF concentrations (all ps>0.05). Conclusion: This preliminary study suggests that the antianhedonic effects of ketamine are not mediated by VEGF.